METHODS FOR STRENGTHENING AND STABILIZATION OF SALINE SOILS IN ROAD CONSTRUCTION (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
Saline soils are among the most problematic geomaterials for road construction in arid and semi-arid regions. This article evaluates chemical, geosynthetic, electrokinetic, and hydraulic methods of improving saline subgrades under the engineering-geological conditions typical of Uzbekistan. Laboratory tests on sulfate-bearing loam with 3.5% salinity showed that the combined use of cement, lime, and bituminous emulsion provided the best overall performance, increasing compressive strength from 0.42 MPa to 2.35 MPa, reducing swelling from 8.4% to 1.4%, and increasing the elastic modulus from 18.5 MPa to 65.2 MPa. An empirical exponential model is proposed to relate stabilized soil strength to salt concentration. Practical recommendations are given for selecting stabilization methods by salinity degree and salt type.